Training at MAN 1 Tanah Datar Plus Skills - Fadriati, Fadriati; Hady, Mulya; Putri, Widya; Afdhol, Muhammad (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this research is to find out about activities to develop the art of reading the Al-Qur'an, which is one of the extra-school activities whose aim is to develop and improve students' recitation skills so that they are able to read the Al-Qur'an well, correctly according to the rules and are able to reciting the rhythm in reading the Koran. This research is training research (Skills). As for the results of the research conducted by the author, it can be concluded that the implementation of coaching the art of reading the Al-Qur'an in improving students' recitation skills at MAN 1 Tanah Datar Plus Skills is still not good, because the implementation is still not running effectively and there are still many obstacles that occur. in these activities. The obstacles in improving recitation skills are, there are still students who are not fluent in pronouncing letters or makharijul letters, as well as recitation, there is no special supervision from the school, then there is a lack of interest and motivation of students, which at the beginning of this activity was held by many. come. Then, only one or two students took part who were serious about taking part. Efforts that must be made are providing motivation and strict supervision from the school for these activities. As well as instilling a sense of love for the Al-Qur'an in students so that they are more enthusiastic in participating in training in the art of reading the Al-Qur'an